Intensive Multicomponent Fibromyalgia Treatment: A Translational Study to Evaluate Effectiveness in Routine Care Delivery. Issue 8 (8th December 2021) - Bruce, Barbara K.; Allman, Madeleine E.; Rivera, Fernando A.; Wang, Benjamin; Berianu, Florentina; Butendieck, Ronald R.; Calamia, Kenneth T.; Hines, Stephanie L.; Rummans, Teresa A.; Niazi, Shehzad K.; Abril, Andy
Abstract : Objective: The current study was designed to evaluate the translation of clinical trial outcomes and clinical guidelines for the treatment of fibromyalgia (FM) into an intensive multicomponent clinical program embedded in routine care delivery. The study aimed to assess the adaptation of these recommended strategies into routine clinical care while evaluating their effectiveness and durability in improving functional status and level of distress in a large clinical sample of FM patients. Methods: Four hundred eighty-nine patients with FM completed a 2-day program that incorporated best practice recommendations for the treatment of FM. Patients completed the Fibromyalgia Impact Questionnaire–Revised, the Center for Epidemiologic Studies Depression Scale, and the Pain Catastrophizing Scale at admission to the program and at follow-up on average 5 months posttreatment. Results: Significant improvements were seen in functional status ( p < 0.0001), depressive symptoms ( p < 0.0001), and pain catastrophizing ( p < 0.0001) after participation in the intensive multicomponent treatment program. Conclusions: The present study shows that an intensive multicomponent treatment program embedded in routine care delivery is effective in significantly improving functional status and psychological distress in a large sample of FM patients. The significant improvements were durable and maintained at follow-up.